2022
DOI: 10.3389/fphar.2022.999017
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: An important target for natural products in the treatment of bone metabolic diseases

Abstract: Bone homeostasis depends on a precise dynamic balance between bone resorption and bone formation, involving a series of complex and highly regulated steps. Any imbalance in this process can cause disturbances in bone metabolism and lead to the development of many associated bone diseases. Autophagy, one of the fundamental pathways for the degradation and recycling of proteins and organelles, is a fundamental process that regulates cellular and organismal homeostasis. Importantly, basic levels of autophagy are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 213 publications
0
3
0
Order By: Relevance
“…found that the PI3K and Akt content decreased in OA ( 18 ), which may lead to a reduction in the PI3K/Akt pathway activity. Then reduces the activity of its downstream target mTOR, a key autophagy inhibitor, resulting in abnormal activation of cellular autophagy in OA and synergistic activation of massive chondrocyte apoptosis in the joint ( 19 ). At the same time, mitochondrial autophagy, a form of selective autophagy, engulfs large amounts of ferritin, leading to excessive Fe 2+ release, increasing the intracellular pool of unstable iron and thus leading to chondrocyte ferroptosis ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…found that the PI3K and Akt content decreased in OA ( 18 ), which may lead to a reduction in the PI3K/Akt pathway activity. Then reduces the activity of its downstream target mTOR, a key autophagy inhibitor, resulting in abnormal activation of cellular autophagy in OA and synergistic activation of massive chondrocyte apoptosis in the joint ( 19 ). At the same time, mitochondrial autophagy, a form of selective autophagy, engulfs large amounts of ferritin, leading to excessive Fe 2+ release, increasing the intracellular pool of unstable iron and thus leading to chondrocyte ferroptosis ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The process of autophagy encompasses not only the osteoclastic resorption process but also the acquisition of energy sources during osteoblast differentiation. 140 Altered autophagy can disrupt bone cell balance, potentially causing various diseases.…”
Section: Autophagy In Bone Metabolismmentioning
confidence: 99%
“…Furthermore, given the unique features of terminal differentiation, the prolonged lifespan of bone cells, and their oxygen and nutrient-deprived environment, autophagy becomes a key player in the regular physiological processes of these cells. 140 , 163 Unsurprisingly, osteocytes exhibit a notable baseline level of autophagy both in laboratory settings and within living organisms. Selectively deleting the autophagy-related gene ATG7 in osteocytes inhibits autophagy, causing decreased bone formation and reduced bone mass in young adult mice, resembling the effects of aging on the skeletal system.…”
Section: Autophagy In Bone Metabolismmentioning
confidence: 99%